Polyether ionophore resistance in a one health perspective - Frederiksen, Rikki Franklin; Slettemeås, Jannice Schau; Granstad, Silje; Lagesen, Karin; Pikkemaat, Mariel G.; Urdahl, Anne Margrete; Simm, Roger (Frontiers in Microbiology, 2024)
Antimicrobial resistance is a major threat to human health and must be approached from a One Health perspective. Use of antimicrobials in animal husbandry can lead to dissemination and persistence of resistance in human pathogens. Polyether ionophores (PIs) have antimicrobial activities and are among the most extensively used feed additives for major production animals. Recent discoveries of genetically encoded PI resistance mechanisms and co-localization of resistance mechanisms against PIs and antimicrobials used in human medicine on transferrable plasmids, have raised concerns that use of PIs as feed additives bear potential risks for human health. This review summarizes the current knowledge on PI resistance and discusses the potential consequences of PI-usage as feed additives in a One Health perspective. Polyether ionophores (PIs) have been used as feed additives for production animals since the early 1970 (Chapman et al., 2010) are among the most extensively used feed additives for production animals across the world. PIs possess both antibacterial and antiprotozoal activity and are currently used in poultry production worldwide to control severe diseases such as coccidiosis caused by Eimeria spp. and necrotic enteritis caused by Clostridium perfringens (Martins et al., 2022). The antibacterial activity of PIs has also proven useful to improve feed conversion in ruminants (